Penerapan Problem Based Learning untuk Meningkatkan Kemampuan Berpikir Analisis Fisika Siswa SMA - Nirwana Nirwana; Dewi Sartika; Arie Arma Arsyad (Jurnal Pendidikan dan Pembelajaran, 2021)
The aims of the research was to find out the level of students analytical thinking skills in physics before and after the applied Problem Based Learning (PBL) model. The research were used pre-experimental with a one-group pretest-posttest design. The sample studied was 23 students of class X MIPA SMA Negeri 1 Pamboang who were selected by purposive sampling technique. The data collection instrument was in the form of an essay test to measure students' analytical thinking skills before and after treatment. Data were analyzed using descriptive and inferential analysis. The average value of pretest was 27,13, while the average value of pottest was 47,34. The price of ttable = 2,073 while tcount = 3,6213. It means that there is a significant increase before and after the implementation of the Problem Based Learning (PBL) learning model.